Prekmurje Agricultural Terminology in the Dolinsko Region - Koletnik, Mihaela (Slavia Centralis, 2020)
The paper presents the dialectal vocabulary of agricultural items in Črenšovci in the Dolinsko region of Prekmurje, with a focus on agricultural tools, crops, as well as field and stable work. The study is based on a thematically defined vocabulary gathered through fieldwork and with the help of questionnaires, pictures and informants’ narratives. It includes archaic vocabulary that is gradually disappearing and is known only to the oldest generation of speakers, as well as the contemporary vocabulary that has been introduced along with the modern technology and is used by the younger generation of speakers.
Keywords: dialectology; Pannonian dialect group; Prekmurje dialect; agricultural terminology; Črenšovci